In Vitro Antidiabetic and Antibacterial Activities of Extracts of Swertia chirayita and Its Substitutes - Oli, Purna Bahadur; Pant, Deepak Raj; Joshi, Giri Prasad; Chaturwedi, Shasi Bhushan (Amrit Research Journal, 2024)
Species of the genus Swertia are among the important medicinal plants used for the treatment of various ailments in traditional medicinal systems like Ayurveda, Siddha, Sowa Rigpa, etc. The therapeutic use of these species is attributed to the presence of bitter principles in their extracts. The present study involves evaluation of antidiabetic and antibacterial activities of aqueous and methanol extracts of eight different species of Swertia from Nepal. The antidiabetic activity was evaluated by using an enzyme inhibition assay for α-amylase and α-glucosidase in vitro while antibacterial activity was evaluated by using an agar well diffusion assay. The extracts of different species showed a strong α-amylase inhibitory activity and weak to moderate α-glucosidase inhibition activity. Antibacterial activity was observed only for the methanol extracts and that also at the high concentrations of the extracts used. The results justify the inclusion of these species in different formulations used for controlling diabetes in various systems of traditional medicine.